How many taxa can be recognized within the complex Tillandsia capillaris (Bromeliaceae, Tillandsioideae)? Analysis of the available classifications using a multivariate approach. - Castello, Lucía Virginia (2013)
Tillandsia capillaris Ruiz & Pav., which belongs to the subgenus Diaphoranthema is distributed in Ecuador, Peru, Bolivia, northern and central Argentina, and Chile, and includes forms that are difficult to circumscribe, thus considered to form a complex. The entities of this complex are predominantly small-sized epiphytes, adapted to xeric environments. The most widely used classification defines 5 forms for this complex based on few morphological reproductive traits: Tillandsia capillaris Ruiz & Pav. f. capillaris, Tillandsia capillaris f. incana (Mez) L.B. Sm., Tillandsia capillaris f. cordobensis (Hieron.) L.B. Sm., Tillandsia capillaris f. hieronymi (Mez) L.B. Sm. and Tillandsia capillaris f. virescens (Ruiz & Pav.) L.B. Sm. In this study, 35 floral and vegetative characters were analyzed with a multivariate approach in order to assess and discuss different proposals for classification of the Tillandsia capillaris complex, which presents morphotypes that co-occur in central and northern Argentina. To accomplish this, data of quantitative and categorical morphological characters of flowers and leaves were collected from herbarium specimens and field collections and were analyzed with statistical multivariate techniques. The results suggest that the last classification for the complex seems more comprehensive and three taxa were delimited: Tillandsia capillaris (=Tillandsia capillaris f. incana-hieronymi), Tillandsia virescens s. str. (=Tillandsia capillaris f. cordobensis) and Tillandsia virescens s. l. (=Tillandsia capillaris f. virescens). While Tillandsia capillaris and Tillandsia virescens s. str. co-occur, Tillandsia virescens s. l. is restricted to altitudes above 2000 m in Argentina. Characters previously used for taxa delimitation showed continuous variation and therefore were not useful. New diagnostic characters are proposed and a key is provided for delimiting these three taxa within the complex.